Analisis Parameter Kualitas Air Sungai Batang Ombilin di Nagari Limo Koto Kecamatan Koto VII Kabupaten Sijunjung Tahun 2025 - Afridon; Kalasta Ayunda Putri; Aulia Rahmi Cheni; Oktamianiza; Vitratul Ilahi (Buletin Keslingmas, 2025)
Batang Ombilin River in Nagari Limo Koto, Koto VII District, Sijunjung Regency, is the main water source for the local community, used for domestic needs, agriculture, and other economic activities. However, the water quality of this river has declined due to human activities such as agriculture, settlements, and illegal gold mining (PETI). This decline in water quality has the potential to impact public health, leading to an increase in cases of skin diseases and diarrhea in the surrounding areas. This study aims to analyze the water quality of the Batang Ombilin River through testing physical and chemical parameters, including temperature, color, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). Water samples were taken from three points (upstream, middle, downstream) and analyzed in the laboratory. The research results show that the parameters of temperature, TDS, BOD, and COD still meet the quality standards for Class II according to Government Regulation No. 22 of 2021. However, color and TSS parameters exceeded standard limits at some points, especially near community and mining activities. In conclusion, although the water quality remains safe for most parameters, there are indications of pollution that require further attention. Regular monitoring and public education are needed to prevent further degradation of water quality.